Vietnamese version of the self-regulated motivation for improving speaking English as a foreign language (VV-SRMIS-EFL): validation and speaking score correlations - Truong, Thi Nhu Ngoc (Frontiers in Education, 2025)
Increased attention has been given to the role of self-regulation and motivation in second language acquisition, particularly in enhancing English-speaking proficiency. This study investigates the psychometric properties of the Vietnamese Version of the Self-Regulated Motivation for Improving Speaking English as a Foreign Language (VV-SRMIS-EFL) among 414 English majors at a public university in Vietnam. Grounded in Pintrich's Self-Regulated Learning Model, the scale assesses four dimensions: Task Value Activation, Regulation of Learning Environment, Regulation of Affect, and Regulation of Peers. The VV-SRMIS-EFL demonstrated strong internal consistency (Cronbach's α = 0.89) and acceptable convergent validity (AVE = 0.55). Descriptive and correlational analyses revealed high levels of self-regulated motivation among participants, with Task Value Activation, Regulation of Peers and Regulation of Affect showing significant positive associations with speaking achievement scores. These findings highlight the relevance of motivational regulation in developing speaking skills and underscore the need for pedagogical and policy interventions that support self-regulated learning strategies in Vietnamese EFL contexts.